Full-thickness resection device for management of lesions involving the appendiceal orifice: Systematic review and meta-analysis - Obri, Mark; Ichkhanian, Yervant; Brown, Patrick; Almajed, Mohamed Ramzi; Nimri, Faisal; Taha, Ashraf; Agha, Yasmine; Jesse, Michelle; Singla, Sumit; Piraka, Cyrus; Zuchelli, Tobias E. (Endoscopy International Open, 2023)
Background and study aims Endoscopic resection of lesions involving the appendiceal orifice is technically challenging and is commonly referred for surgical resection. However, post-resection appendicitis is a concern. Many studies have varying rates of post-procedure appendicitis. We aim to report the rate of post-resection appendicitis by performing a systematic review and meta-analysis.Methods Studies that involved the use of a full-thickness resection device (FTRD) for management of appendiceal polyps were included. The primary outcome was appendicitis after FTRD and a subgroup analysis was performed on studies that only included FTRD performed at the appendiceal orifice.Results Appendicitis was encountered in 15% (95%CI: [11–21]) of the patients with 61% (95% CI: [44–76]) requiring surgical management. Pooled rates of technical success, histologic FTR, and histologic R0 resection in this sub-group (n=123) were 92% (95% CI: [85–96]), 98% (95% CI: [93–100]), and 72% (95% CI: [64–84%]), respectively. Post-resection histopathological evaluation revealed a mean resected specimen size of 16.8 ± 5.4 mm, with non-neoplastic pathology in 9 (7%), adenomas in 103 (84%), adenomas + high-grade dysplasia (HGD) in nine (7%), and adenocarcinoma in two (2%). The pooled rate for non-appendicitis-related surgical management (technical failure and/or high-risk lesions) was 11 % (CI: 7–17).Conclusions FTRD appears to be an effective method for managing appendiceal lesions. However, appendicitis post-resection occurs in a non-trivial number of patients and the R0 resection rate in appendiceal lesions is only 72%. Therefore, caution should be employed in the use of this technique, considering the relative risks of surgical intervention in each patient.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Endoscopy Lower GI Tract; Tissue diagnosis; GI Pathology; Polyps/adenomas/...